Antibiogram Profile of Bacteria Colonizing the Endotracheal Tubes (ETTs) of Patients Admitted to Intensive Care Units (ICUs) in a Tertiary Care Hospital of Nepal - Shrestha, Rajani; Nayak, Niranjan; Bhatta, Dharm Raj; Hamal, Deependra; Gokhale, Shishir; Parajuli, Sulochana (Nepal Medical College Journal, 2021)
Hospital acquired infection (HAI) in intensive care units (ICU) are responsible for high morbidities and mortalities worldwide due to emergence of resistant bacteria. In developing countries, due to lack of knowledge of proper surveillance, proper resources and proper guidance this burden was somewhat underestimated. Thus, the aim of this study was to look for the spectrum of bacteria colonizing the ETTs and to determine proper empirical antibiotic therapy. We collected endotracheal tube aspirates from 188 patients of admitted in ICU of Manipal Teaching Hospital, Pokhara. All bacteria were identified by conventional techniques. Antimicrobial sensitivity testing was performed on Mueller-Hinton agar plates with commercially available antibiotic discs using Kirby-Bauer disc diffusion techniques and interpreted as per the guidelines of CLSI. The antibiotic discs (conc.) used were: piperacillin/tazobactam (100/10mcg), ciprofloxacin (5mcg), amikacin (30mcg), imipenem (10mcg), gentamicin (10mcg), cefaperazone sulbactum(75/10mcg), for Gram negative bacteria and erythromycin (15mcg), amikacin (30mcg), gentamicin (10mcg), ciprofloxacin (5mcg), and clindamycin (2mcg) for Gram positive bacteria. A total of 188 ETTs investigated, 128(68.08%) yielded positive culture. Single type of organisms was found in 119 (63.29%) and 9 (4.7%) cases yielded mixed type of growth. Acinetobacter spp. were the most predominant organism among all gram-negative organisms, which was found to be in 71 (51.82%) cases, followed by Klebsiella pneumoniae in 27 (19.7%), Pseudomonas aeruginosa in 23 (16.78%), Escherichia coli in 5 (3.64%), Enterobacter in 2 (1.46%). Whereas, Staphylococcus aureus (4.37%) was the commonest among all gram-positive organism followed by coagulase negative Staphylococcus in 2 (1.46%) and Enterococcus in 1 (0.73%). Most of Acinetobacter spp. showed resistance to ciprofloxacin (84.5%), while 74.6% were resistant to amikacin, 73.2% to gentamicin, 71.83% to piperacillin-tazobactam and 42.2% towards imipenem. Out of the 6 strains of S. aureus, 5 (83.3%) were methicillin resistant. Due to the increasing incidence of organisms in ICUs, an early and correct diagnosis of ETT associated infections is a challenge for optimal antibiotic therapy. Therefore, the best approach to manage the respiratory infections following ETT application will be appropriate use of antibiotics with adaptation of proper infection control measures, which could help to prevent further spread of infection.